Association between ticagrelor plasma concentration and bleeding events in Chinese patients with acute coronary syndrome. Issue 11 (19th June 2022) - Yang, Jing; Qi, Guangzhao; Hu, Fudong; Zhang, Xiaojian; Xing, Yu; Wang, Peile
Abstract : Aims: The risk of ticagrelor‐related bleeding events remains a major clinical concern, especially in East Asian populations. Previous studies have reported higher ticagrelor exposure in Asian patients than in Caucasians. This prompted us to investigate the correlation between ticagrelor concentrations and bleeding events. Methods: Patients diagnosed with acute coronary syndrome and receiving dual antiplatelet therapy (aspirin and ticagrelor) were enrolled and followed up for 12 months. Trough plasma concentrations of ticagrelor and a major active metabolite were assayed, and 10 single nucleotide polymorphisms associated with ticagrelor pharmacokinetics and safety were also identified. Results: A total of 631 patients were included and 133 patients had bleeding academic research consortium type 1 or 2 bleeding event. The median ticagrelor concentration (interquartile range) was significantly higher in patients with bleeding events than that in patients without bleeding events (322.6 ng/mL [196.2–458.0 ng/mL] vs . 222.1 ng/mL [140.4–341.9 ng/mL], P < .001). According to the receiver operating characteristic curve, the cut‐off value for ticagrelor levels predicting bleeding events was 363.3 ng/mL (area under the curve = 0.65; P < .001, 95% Cl: 0.595–0.700). Pharmacogenomics results showed that P2Y12 (rs6787801, P = .024) and P2Y12 (rs6785930, P = .048) were statistically associated with ticagrelor levels and bleeding events, respectively. Conclusion: Ticagrelor plasma concentrations were associated with bleeding events in Chinese patients with acute coronary syndrome.